Comprehending the Notion of Publicness: Unexplored Dimensions and Future Research Initiatives - khairul muluk, `mujibur rahman; Sajida, Sajida; Nisa, Gina De; Durrety, Shinta Fatimah (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2023)
This research delves into the multifaceted nature of publicness, offering insights into areas in the field of public administration. In times, the importance of publicness has grown significantly as it plays a role in shaping interactions among the public sector, private organizations, and civil society. Despite the available literature on publicness, there remain a few underexplored aspects that merit further investigation. This study reviewed the existing literature to identify and analyze gaps in research on publicness. By examining various perspectives, theoretical frameworks, and relevant aspects related to publicness, we discovered domains where scholarly discussions have notably lacked attention. The results of this study demonstrate that the concept of publicness encompasses a diverse range of theoretical perspectives, such as the management of publicness, public-private partnerships, governance, and the provision of public goods. Each element provides a distinct contribution to the comprehension of publicness in public administration. Moreover, this study highlights issues discussed in publicness, including public enterprises, public leadership, public facilities, public interest, public-private partnerships, governance, public goods, public space, public organizations, public value, and public service. These findings lead to a proposal for further research initiatives in publicness.